The effect of continuous and interval muscular endurance training on some cardiorespiratory variables and trained runners' records - مهرزاد عبادی قهرمانی; بهمن تاروردی زاده; مقصود پیری; حمید آقا علی نژاد (Shahid Beheshti University, 2015)
purpose: This study was designed to investigate the effect of continuous and interval muscular endurance trainingon some structural and functional cardio respiratory variables and trained runners' records. Methodology: 27 youngmen voluntarily participated in this study. After the introduction session, based on the one-mile record, the subjectswere randomly assigned to three groups, namely, interval group, continuous group, and control group, with a mean(±SD) (19.89 ± 3.40 yr , 186.04 ± 5.23 cm , 77.97 ± 8.55 kg). In order to measure the structural and functionalcardiac variables, two-dimensional and Doppler echocardiograms were used. All The Participants performed theexercises in three sessions per week for 8 weeks. For statistical analysis, a one-way ANOVA and the Bonferronipost hoc test were utilized. Results: The eight- week continuous and interval muscular endurance training had asignificant effect on the variables under study (p< 0.05). The results indicated that it had the greatest effect onmaximal oxygen consumption, maximum aerobic speed, anaerobic threshold velocity, and left ventricular ejectionfraction, and runners' records in the interval group, and on the stroke volume in the continuous group. With regardto the intra ventricular septum and maximum exhaustion, there was no statistically significant difference amonggroups. Conclusion: The results indicated that for the purpose of enhancing some variables, which have beenstrengthened via continuous training, interval training can also be as beneficial.